Pengaruh Lingkungan Kerja Dan Disiplin Kerja Terhadap Kinerja Karyawan PT Rumah Sakit PELNI Jakarta Barat - Febriyanti, Febriyanti; Rani (Jurnal Mnajemen | Ekonomi | Akuntansi, 2025)
PT Rumah Sakit PELNI is a state-owned hospital located in West Jakarta. This study aims to determine the partial and simultaneous effects of the work environment and work discipline on employee performance. The type of research data used is quantitative, utilizing multiple linear regression analysis, with data processed using SPSS. This study employed a non-probability sampling approach to select 54 employees as the population. The data sources used include primary data such as observations and questionnaires, as well as secondary data from literature studies through books and journals. The results of this study indicate that the work environment has a positive and significant partial effect on employee performance. The work discipline variable also has a positive and significant partial effect on employee performance. Furthermore, the work environment and work discipline variables have a simultaneous and significant effect on employee performance. Based on the R-Square (R²) determination coefficient test, the work environment and work discipline contribute 72.1% to employee performance.